The Review of Employee Rewards on Employee Motivation: Toxic Environment as a Moderating Variable - Mdhlalose, Dickson Scotch (Universitas Mercu Buana, 2025)
Research Aims: Employee rewards are a crucial tool for motivating employees and recognizing their contributions to the organization. However, organizations frequently overlook the elements (financial and non-financial rewards) that motivate employees. Most organizations lack the tools and tactics to motivate employees, and the worst part is that a toxic work environment demotivates employees. This study aims to investigate and understand how employees’ rewards affect their motivation in a toxic environment as a moderating variable. Design/Methodology/Approach: Exploratory research was used to approach this review. The information was gathered from online publications, dissertations, online databases, and books relevant to the topic. Research Findings and Implications: Financial benefits are the most effective motivator for most employees; however, select individuals are driven by intrinsic rewards. Money alone is not always sufficient to motivate employees. A toxic workplace environment demotivates employees regardless of the rewards. Theoretical Contribution/Originality: The importance of this research study is that it expands on the substantial amount of literature that is currently accessible concerning how employee rewards affect employee motivation. Research Limitation: The study's boundaries were limited to secondary sources that were easily accessible online, the impact of employee rewards on motivation, and related issues. Secondary sources may occasionally be out of date or inaccurately reflect the most recent techniques or technological advancements in the sector.